2017
DOI: 10.18311/jnr/2017/17938
|View full text |Cite
|
Sign up to set email alerts
|

Metformin - A Panacea Pharmaceutical Agent through convergence revolution initiative

Abstract: Metformin has been known to the mankind for centuries. Metformin is the first line of drug of choice for the treatment of type 2 diabetes. Initial pharmaceutical therapy was for treating the frequent urinal problem which is a primary manifestation of diabetes. At the time of writing, metformin as an intervention is looked into for cardiovascular risks, polycystic ovary syndrome and breast cancer. Annual demand for Metformin is 23,000 Metric tons per annum. Nano Drug Delivery Systems (NDDS) has embarked into Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The global consumption of metformin is expected to increase with the continuously growing diabetes population (it is projected that 784 million adults will be living with diabetes by 2045) 1 and the expanding panacea nature of metformin (e.g., recently demonstrated to alleviate COVID-19). 3,4 Thus, it is foreseeable that the contamination of metformin in global waters and the adverse risks associated with long-term exposure to metformin and its TPs will be enhanced over time. To protect the drinking water supply and the health of ecosystems and humans, we suggest to strengthen the following research aspects in future studies:…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The global consumption of metformin is expected to increase with the continuously growing diabetes population (it is projected that 784 million adults will be living with diabetes by 2045) 1 and the expanding panacea nature of metformin (e.g., recently demonstrated to alleviate COVID-19). 3,4 Thus, it is foreseeable that the contamination of metformin in global waters and the adverse risks associated with long-term exposure to metformin and its TPs will be enhanced over time. To protect the drinking water supply and the health of ecosystems and humans, we suggest to strengthen the following research aspects in future studies:…”
Section: Discussionmentioning
confidence: 99%
“…The global consumption of metformin is expected to increase with the continuously growing diabetes population (it is projected that 784 million adults will be living with diabetes by 2045) and the expanding panacea nature of metformin (e.g., recently demonstrated to alleviate COVID-19). , Thus, it is foreseeable that the contamination of metformin in global waters and the adverse risks associated with long-term exposure to metformin and its TPs will be enhanced over time. To protect the drinking water supply and the health of ecosystems and humans, we suggest to strengthen the following research aspects in future studies: Monitoring of metformin contamination in global waters, especially stormwater, groundwater, drinking water sources, and tap water where TPs with enhanced toxicity will be generated following disinfection; special attention should be given to regions with a high prevalence of diabetes but little available data and/or to middle-income countries, such as nations in the Middle East, South America, and Africa. Investigation of the transformation pathways and mechanisms of metformin and the development of full mineralization technologies to minimize the production of problematic TPs. Development of the analytical standards for TPs and improvements in studies on the analysis and monitoring of toxic TPs along with metformin in wastewater, surface water, and drinking water. Further exploration of the endocrine-disrupting effects of metformin and its TPs on fish and the establishment of biomarkers. The adverse effects, particularly chronic effects, of TPs to species in different trophic levels, or the long-term exposure risk of TPs with high predicted toxicity at environmentally relevant concentrations as well as the synergistic, antagonistic, and additive effects of degradation mixtures. Assessment of the health risks of metformin and TPs in surface water and drinking water, particularly the risks to sensitive species and children in heavily contaminated regions such as Lagos, Nigeria. The continuous refinement of metformin as a robust and universal indicator for pharmaceuticals in wastewater, surface water, and other aquatic systems at regional and global scales, with the increase in relevant publicly available monitoring data. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It lowers blood glucose by stimulating the sensitivity of peripheral tissues to insulin [7]. Reports have implicated metformin in the treatment of polycystic ovary syndrome [8]. Studies have shown that T2DM patients treated with metformin medication responded better to chemotherapy than those placed on sulfonylureas [9].…”
Section: Discussionmentioning
confidence: 99%